Nanotechnology connecting copper metabolism and tumor therapy - Li, Yongjuan; Dong, Ya; Zhou, Xinyao; Fan, Kelong (MedComm - Biomaterials and applications, 2023)
Copper (Cu) is an essential trace element in the human body that is involved in the formation of several natural enzymes, such as superoxide dismutase and cyclooxygenase. Due to the high density of the outer electron cloud of Cu, which allows the transfer of multiple electrons, Cu is often used as the catalytic center in various metabolic enzymes. However, both deficiency and excessive accumulation of Cu can result in irreversible damage to cells. Therefore, strategies to regulate Cu metabolism, such as Cu exhaustion and Cu supplementation, have emerged as attractive approaches in anticancer therapy, due to the potential damages caused by Cu metabolism disorders. Notably, recent advancements in nanotechnology have enabled the development of nanomaterials that can regulate Cu metabolism, making this therapy applicable in vivo. In this review, we provide a systematic discussion of the physical and chemical properties of Cu and summarize the applications of nanotechnology in Cu metabolism‐based antitumor therapy. Finally, we outline the future directions and challenges of nano‐Cu therapy, emphasizing the scientific problems and technical bottlenecks that need to be addressed for successful clinical translation. Copper metabolism is emerging as a therapeutic strategy for cancer treatment, and nanotechnology is being used to connect copper and tumor therapy. Copper deficiency and excess accumulation can cause cell damage, and nanotechnology is being used to reduce side effects and enhance therapeutic effects.